2018
DOI: 10.3897/compcytogen.v12i1.20334
|View full text |Cite
|
Sign up to set email alerts
|

The genome structure of Arachis hypogaea (Linnaeus, 1753) and an induced Arachis allotetraploid revealed by molecular cytogenetics

Abstract: Peanut, Arachis hypogaea (Linnaeus, 1753) is an allotetraploid cultivated plant with two subgenomes derived from the hybridization between two diploid wild species, A. duranensis (Krapovickas & W. C. Gregory, 1994) and A. ipaensis (Krapovickas & W. C. Gregory, 1994), followed by spontaneous chromosomal duplication. To understand genome changes following polyploidy, the chromosomes of A. hypogaea, IpaDur1, an induced allotetraploid (A. ipaensis × A. duranensis)4x and the diploid progenitor species were cytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 67 publications
9
18
0
Order By: Relevance
“…Cultivated peanut is an allotetraploid (AABB genome) with a genome size of 2.7 Gb (Dhillon et al, 1980;Bertioli et al, 2016;Nascimento et al, 2018). It's inbred nature, recent domestication, perhaps single polyploidization event, and the presence of crossing barriers between the cultivated species lines and its wild diploid relatives contribute to the paucity of genetic polymorphism within this species.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivated peanut is an allotetraploid (AABB genome) with a genome size of 2.7 Gb (Dhillon et al, 1980;Bertioli et al, 2016;Nascimento et al, 2018). It's inbred nature, recent domestication, perhaps single polyploidization event, and the presence of crossing barriers between the cultivated species lines and its wild diploid relatives contribute to the paucity of genetic polymorphism within this species.…”
Section: Introductionmentioning
confidence: 99%
“…The Xingu accessions had two pairs of chromosomes displaying CMA 3 + bands, situated on the proximal regions of the chromosomes A10 and B10 ( Figures 3A, B) and representing the sum of CMA 3 + bands observed in A. duranensis and A. ipaënsis (Nascimento et al, 2018). These bands differed from those present in the other tetraploids studied.…”
Section: Distribution Of Heterochromatic Bandingmentioning
confidence: 94%
“…Genome structural variations represent large rearrangements of genomic types including deletion, insertion, inversions, duplications and copy number variations [31]. It was reported that at least one pair of chromosomes of IpaDur1, an induced allotetraploid (A. ipaensis  A. duranensis) 4x , has a clear mosaic hybridization pattern indicating recombination between the subgenomes [7]. According to the homology of sequences, most of mTERFs in allotetraploid peanut were obtained from wild diploid, such as AhmTERF1-7, AhmTERF11, AhmTERF13-15, AhmTERF35-36 and AhmTERF50-51.…”
Section: Identification and Phylogenetic Analysis Of Allotetraploid Pmentioning
confidence: 99%
“…Cultivated peanut (Arachis hypogaea) is an allotetraploid species (AABB genome, 2n ¼ 4x ¼ 40) whose ancestral genomes are probably derived from the Agenome species, A. duranensis (AA genome, 2n ¼ 2x ¼ 20), and the B-genome species, A. ipaensis (BB genome, 2n ¼ 2x ¼ 20) [2][3][4]. The hybridization event between two diploid species most likely resulted in the allotetraploid A. hypogaea [4][5][6][7], which occurred about 11,690 years ago and the domestication of A. hypogaea happened about 4500 years ago [8].…”
Section: Introductionmentioning
confidence: 99%